Genetic analysis and combining ability in okra (Abelmoschus esculentus L.) - Balagoni, M; Sibsankar, D; Arup, C; Umesh, T; Anirban, M; Pranab, H; Chandan, K; Bandari, N (Plant Science Today, 2025)
Okra a widely cultivated vegetable crop in tropical and subtropical regions of the world, that is valued for its significant nutritional and therapeutic properties. The current investigation was conducted with 21 F1 hybrids developed through a half-diallel mating design by using seven diverse parental lines namely, Punjab-8, Hissar Unnat, Hoshiarpur Local, Anima, Green Gold, Ajeet 121 and AKO 107 which were evaluated during the rainy season, 2022 and spring-summer, 2023 in randomized block design with three replications. Significantly highest general combining ability (GCA) effect for fruit production per plant was displayed by parent Hissar Unnat in both seasons of investigation followed by Punjab 8. These two parents have a good scope in the yield improvement program. In terms of disease resistance substantial GCA impacts in the intended direction for tolerance to bhindi yellow vein mosaic virus (BYVMV) and okra enation leaf curl virus (OELCV) were shown by the parents AKO-107 and Ajeet 121, respectively in both seasons of investigation. Both Ajeet 121 and AKO 107 were established to be ideal general combiners for disease resistance. Maximum substantial specific combining ability (SCA) impacts in the positive direction for fruit production per plant along with tolerance to OELCV and BYVMV were observed in crosses Punjab 8 × Ajeet 121 and Hissar Unnat × AKO 107 during the investigation. These promising crosses, involving at least one ideal general combiner parent, offer significant potential for developing superior segregating lines. The predictability ratio confirmed the overwhelming influence of non-additive gene action for regulating all the evaluated traits.